Retention and clinical response to abatacept in patients with rheumatoid arthritis: an Italian perspective - Galeazzi, Mauro; Lorenz, Hanns-Martin (Clinical and experimental rheumatology, 2018)
Letters to the Editor; Authors: Mauro Galeazzi, Rieke Alten, Melanie Chartier, Yedid Elbez, Enrico Fusaro, Manuela Le Bars, Hanns-Martin Lorenz, Giuseppa Pagano Mariano, Maurizio Muratore, Hubert G. Nüßlein, Giovanni Patanè
Gesehen am 12.12.2019
Keine DOI vorhanden